2001
DOI: 10.1002/jmv.1017
|View full text |Cite
|
Sign up to set email alerts
|

Use of bacterially expressed EBNA‐1 protein cloned from a nasopharyngeal carcinoma (NPC) biopsy as a screening test for NPC patients

Abstract: EBV serological tests have been used for many years as accessory diagnostic predictors of nasopharyngeal carcinoma (NPC). To increase the sensitivity and specificity of the NPC detection rate, a novel enzyme-linked immunosorbent assay (ELISA) was established using a bacterially-expressed GST-EBNA-1 protein, containing the EBNA-1 sequence cloned from an NPC patient. Serum samples were collected from age- and gender-matched patients with NPC, community control subjects and hospital control patients and tested us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
18
0

Year Published

2004
2004
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(21 citation statements)
references
References 26 publications
(23 reference statements)
3
18
0
Order By: Relevance
“…However, the IgA EBNA1 ELISA was positive in only 3.6%, 11.1%, and 16.6% of healthy EBV carriers, patients with lymphoma and patients with autoimmune diseases, respectively. These findings were in agreement with South East Asia series which have demonstrated higher sensitivity and specificity of IgA ELISA in patients with nasopharyngeal carcinoma by using recombinant C-terminal domain (aa 390-641) [Chen et al, 1996[Chen et al, , 2001Hu et al, 2007] or polypeptide synthetic (aa 382-410 and 413-452) [Fachiroh et al, 2006] of EBNA1 as coating antigen. They also found that the complementary combination of EBNA1 protein with EA-p47/54 or VCA-p18 [Fachiroh et al, 2006;Hu et al, 2007] increases the sensitivity of the detection of nasopharyngeal carcinoma.…”
Section: Discussionsupporting
confidence: 93%
“…However, the IgA EBNA1 ELISA was positive in only 3.6%, 11.1%, and 16.6% of healthy EBV carriers, patients with lymphoma and patients with autoimmune diseases, respectively. These findings were in agreement with South East Asia series which have demonstrated higher sensitivity and specificity of IgA ELISA in patients with nasopharyngeal carcinoma by using recombinant C-terminal domain (aa 390-641) [Chen et al, 1996[Chen et al, , 2001Hu et al, 2007] or polypeptide synthetic (aa 382-410 and 413-452) [Fachiroh et al, 2006] of EBNA1 as coating antigen. They also found that the complementary combination of EBNA1 protein with EA-p47/54 or VCA-p18 [Fachiroh et al, 2006;Hu et al, 2007] increases the sensitivity of the detection of nasopharyngeal carcinoma.…”
Section: Discussionsupporting
confidence: 93%
“…In the cancer screening setting, the sensitivity, specificity, quality control, and costs are relevant considerations. To date, only a few markers or marker panels have been reported to have both a sensitivity and specificity Ͼ90% for detection of NPC (15,17,18,36 ). The sensitivity of 99% of the combined IgA-VCA/EBV DNA marker panel and the specificity of 96 -98% of the respective markers in the present study warrant further studies in the screening setting.…”
Section: Discussionmentioning
confidence: 99%
“…These were based on antibodies to different antigenic components of the EBV (9,(15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29). Attempts to use panels of antibody-based markers have generally been useful in improving the accuracy of NPC detection (13, 15, 20, 21, 29 -32 ).…”
mentioning
confidence: 99%
“…In order to further define the clinical specificity of EBV peptide-based IgA 4. Data analysis of IgA ELISA by using EBNA1 and VCA-p18 as single and combination antigens in NPC patients grouped by stage.…”
Section: Fig 1 the Effect Of Gullsorb In Ebv Peptidementioning
confidence: 99%